Profiling Muslim Youths Behaviors in Relation to Social Media Usage - Aliman, Nor Khasimah; Ariffin, Zailin Zainal; Hashim, Shareena Mohamed; Hassan, Paiz; Anas, Norazmi (Archives of Business Research, 2021)
The present paper provides a general profile of Malaysian Muslim youths behaviors in relation to social media usage. A sample of 400 social media users answered a questionnaire that tackled questions related to technological devices and social media, social media sites visit, preferred social media sites, social change, reasons for using social media, religiosity, social media usage and attitude towards promoting Islam. Using descriptive statistical tools, data analyses were performed on 384 completed survey questionnaires. The study revealed that majority of Muslim youths in Malaysia using mobile phone to browse social media. The top three social media sites visited by the youths are Instagram, YouTube and Facebook. The most preferred social media sites are Facebook, Instagram and YouTube. In addition, social media brought three main social changes to them: 1) I have more friends; 2) My awareness on world issues is increasing; 3) I am more sensitive to human issues. The three main factors influencing them to use social media are lifestyle, availability of technology and IT knowledge. Finally, no difference was found between male and female in relation to social changes and religiosity level. Social media brought many social changes to both male and female youths and the religiosity level of both male and female youths is high. These research findings should offer essential information to social media operators and Malaysian community in general.